Lithuanian health care in transitional state: ethical problems - Žekas Romualdas; Darulis Žilvinas; Jakušovaitė Irayda (BMC, 2005)
Abstract Background Throughout the economic and political reforms in post-communist countries, significant changes have also occurred in public morality. One of the tasks of the Lithuanian health policy is to create mechanisms for strengthening the significance of ethical considerations in the decision-making processes concerning health care of individuals and groups of individuals, as well as considering the positions of physicians and the health care system itself in a general way. Thus, health care ethics could be analyzed at two levels: the micro level (the ethics of doctor-patient relationships) and the macro level (the ethics of health policy-making, which can be realized by applying the principles of equal access, reasonable quality, affordable care and shared responsibilities). To date, the first level remains dominant, but the need arises for our attention to refocus now from the micro level to the patterns of managing and delivering care, managing the health care resources, and conducting business practices. Discussion In attempting to increase the efficiency of health services in Lithuania, a common strategy has been in place for the last fifteen years. Decentralization and privatization have been implemented as part of its policy to achieve greater efficiency. Although decentralization in theory is supposed to improve efficiency, in practice the reform of decentralization has still to be completely implemented in Lithuania. Debates on health policy in Lithuania also include the issue of private versus public health care. Although the approach of private health care is changing in a positive way, it is obvious that reduced access to health services is the most vulnerable aspect. In the Lithuanian Health Program adopted in July 1998, the target of equity was stressed, stating that by 2010, differences in health and health care between various socio-economic groups should be reduced by 25%. Summary The restructuring of health care system in Lithuania should be based on a balance between decentralization and centralization, and between public and private health care sectors. Successful transition requires a balanced role of the government. Today it is obvious in Lithuania that continuous encouragement to make sacrifices was not enough to induce the system to function well, and in an ethical manner.